1999
DOI: 10.1002/j.1551-8833.1999.tb08623.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic uranium activity ratios in California groundwater

Abstract: Whether the uranium MCL is met in California depends on what conversion factor is used. Uranium, a kidney toxicant and a radioactive material, is present at elevated concentrations in groundwater in some states. In 1991 the US Environmental Protection Agency proposed a maximum contaminant level (MCL) for uranium in drinking water of 20 μg/L or 30 pCi/L (1.1 Bq/L). In 1992 California adopted an MCL of 20 pCi/L (0.74 Bq/L). Because California regulations permit analysis of uranium by either mass or radiochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The specific activity of uranium in drinking water generally is higher than that of natural uranium due to an elevated concentration of uranium-234 in drinking water relative to natural uranium (Karpas et al 2005). Typical values for the specific activity of uranium in drinking water in the range 0.8-1.3 pCi µg -1 have been estimated from isotopic compositions of uranium found in public water systems (Federal Register 56, July 18, 1991;Wong et al 1999;EPA 2007b). In the present report, a rounded central estimate of 1 pCi µg -1 is used as the specific activity of uranium in drinking water and for consistency is also applied to air.…”
Section: Resultsmentioning
confidence: 99%
“…The specific activity of uranium in drinking water generally is higher than that of natural uranium due to an elevated concentration of uranium-234 in drinking water relative to natural uranium (Karpas et al 2005). Typical values for the specific activity of uranium in drinking water in the range 0.8-1.3 pCi µg -1 have been estimated from isotopic compositions of uranium found in public water systems (Federal Register 56, July 18, 1991;Wong et al 1999;EPA 2007b). In the present report, a rounded central estimate of 1 pCi µg -1 is used as the specific activity of uranium in drinking water and for consistency is also applied to air.…”
Section: Resultsmentioning
confidence: 99%
“…Vapor-liquid fractionation factors for C, Cl and H in TCE were discussed for its utility in investigating sites with soil vapor extraction or soil bioventing operations. Wong et al (1999) measured the relative abundance of the uranium isotopes U-234 and U-238 in groundwaters in California using three mass measurement techniques and two radiochemical techniques. Based on the activity and mass ratios, they calculated a mass-to-conversion factor of 0.79 pCi/μL, which was recommended to be the basis for estimating total U in water sources in California.…”
Section: New Sample Preparation Techniques and Data Analysismentioning
confidence: 99%
“…Throughout several decades, a number of studies have reported large variations in groundwater ( 234 U/ 238 U) across different geological settings with essentially ubiquitous ( 234 U/ 238 U) > 1.0 (Cowart, 1981; Cuttell et al, 1988; Gilkeson et al, 1984; Herczeg et al, 1988; Hussain & Krishnaswami, 1980; Osmond et al, 1983; Paces et al, 2002). Given the potential impacts of variable ( 234 U/ 238 U) on drinking water regulations, Wong et al (1999) surveyed the isotopic variation in California groundwaters prior to the revised radionuclide rule to explore whether an appropriate conversion factor from mass to activity could be determined in a specific region. They found ( 234 U/ 238 U) from 0.78 to 2.27 and suggested a conversion factor of 0.79 pCi/μg based on an average ( 234 U/ 238 U) ratio of 1.32.…”
Section: Introductionmentioning
confidence: 99%